Digital edition and management in the public library - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2011)
With the advent of digital books it is recommended that librarians take an active role, defending the rights of citizens to be able to continue enjoying free reading, and also maintaining their own image of being up-to-date professionals. Librarians should know technical, economic and legal details of the publishing world to act on new fronts, such as being literary agents, promoters of issues of local interest or licensing consultants.
Keywords: Ebooks; Electronic books; Digital edition; Information professional; Librarian; Management; Open formats